Does Hijrah Trends Create a Different Decision on Behavior Consumption of Indonesian Muslims? - Irma Yuliani; Alif Khuwarazmi (Bulletin of Islamic Economics, 2022)
The growth of digital activity in human life has an impact on hijrah activities among Indonesian Muslims. Digital activities have encouraged the spirit of Indonesian muslim through religious persuasion from figures who become their role models (their idols), including reciter of holy Qur’an (qari’), asatidz, da'i, Muslim celebrities, singer of nasyid and other figures. Not everyone sees the trend, although in religious perspective the hijrah activities still reap a lot of controversy, but in other hand these activities have a diffirent impact on the economic sector. This study aims to investigate the impact of hijah trend of Indonesian muslim on the consumer decision to consume halal product in Indonesia. The sample of this study collected from some populations in Indonesia. To observe the specific characteristics, this study will devide the socio economic and demographic character through three regional classifications, consisting of eastern Indonesia, central Indonesia, and western Indonesia. The variables that employed in this study are religiosity, socio economic and demographic, and also the product attribute to find the impact of hijrah trend on the consumer decision to consume halal product (food, islamic modest fashion, cosmetic) in Indonesia. The method that used in this study is quantitative using Theory Planned Behavior approaches that was analyzed with Structural Equation Modelling-Partial Least Square (SEM-PLS) approach. The results show, the consideration of religiosity of Indonesian muslim to consume halal product increasingly grow when driven by spirit of hijrah of Indonesian muslim. Beside that, variabel Religiosity, islamic branding, persuasive marketing, product quality, appetite, price also accepted empically.